2017
DOI: 10.3171/2017.8.focus17437
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of early chemical deep venous thrombosis prophylaxis after spinal cord injury: pilot prospective data

Abstract: OBJECTIVESpinal cord injuries (SCIs) occur in approximately 17,000 people in the US each year. The average length of hospital stay is 11 days, and deep venous thrombosis (DVT) rates as high as 65% are reported in these patients. There is no consensus on the appropriate timing of chemical DVT prophylaxis for this critically injured patient cohort. The object of this study was to determine if low-molecular-weight heparin (LMWH) was safe and effective if given within 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Duplex ultrasound was performed if there was clinical suspicion for DVT/PE. 11,17,26,28,31,38 Routine duplex ultrasounds were not obtained due to the increased cost and resource utilization required for obtaining the study in all SCI patients. PE was confirmed with computed tomography angiography.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Duplex ultrasound was performed if there was clinical suspicion for DVT/PE. 11,17,26,28,31,38 Routine duplex ultrasounds were not obtained due to the increased cost and resource utilization required for obtaining the study in all SCI patients. PE was confirmed with computed tomography angiography.…”
Section: Methodsmentioning
confidence: 99%
“…17,24,29,33 The higher rates of VTE reported by the SCI thromboprophylaxis investigators study may be due to their protocol incorporating routine surveillance with ultrasonography as opposed to our study which did so only when there was clinical suspicion. 36 Multiple studies in the literature have previously utilized clinical suspicion as the trigger to obtain the duplex ultrasound 11,17,26,28,31,38 and a recent systematic review found insufficient evidence to support the hypothesis that routine surveillance decreases VTE-associated morbidity/mortality. 34 Aito et al 36 performed a direct comparison of 275 consecutive acute SCI patients and found a low rate of DVT in those who received LMWH within 72 hours of injury (2%), which was a significantly lower DVT rate than in those with delayed LMWH administration 8-28 days after injury (26%).…”
Section: Timing Of Chemoprophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of starting thromboprophylaxis has been examined in observational studies. [39][40][41][42] A prospective study evaluated the efficacy of using a protocol for prevention of VTE in 275 patients with acute SCI based on concomitant use of nadroparin 0.4 mL once daily and combination of external sequential pneumatic compression (ESPC), permanently dressed gradient elastic stockings, and early mobilization of the lower limbs. 39 Prophylaxis was administered to 99 patients within 72 hours (early-admitted patients), while the other group of 176 patients (late-admitted patients) received prophylaxis from 7 to 28 days postinjury (mean 12 days).…”
Section: Optimal Timing Of Starting Low-molecular-weight Heparinmentioning
confidence: 99%
“…The TRACK-SCI evaluated the safety and effectiveness of early start of enoxaparin 40 mg once daily within 24 hours of injury in a pilot prospective study. 41 Forty-nine patients were enrolled from May 2015 to March 2017. There were three symptomatic DVTs (6.1%) and two PEs (4.1%) despite thromboprophylaxis.…”
Section: Optimal Timing Of Starting Low-molecular-weight Heparinmentioning
confidence: 99%